The Cost of Diagnosis of Leprosy by Active Case Detection in Kailali, Nepal - Baskota, Rabindra; Rupakheti, Dinesh; Rai, Anjan; Gyawali, Bikram; Baral, Rashmi (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Leprosy is a is a chronic infectious disease caused by Mycobacterium leprae. Current modalities for early diagnosis of leprosy include active case detection campaigns, contact tracing, and skin camps. Active case detection is an effective strategy that enables early treatment, prevents impending disability, and potentially stops the spread of leprosy. Objectives: This study was conducted to determine the cost of early diagnosis of leprosy by active case detection method in Lamkichuha Municipality of Kailali district. Materials and Methods: In coordination with the Municipality, Leprosy Control and Disability Management Section of Ministry of Health and Population conducted a survey in July of 2022. Using active case detection method, orientation on leprosy was given to health workers followed by household visit and screening of skin lesions suggestive of leprosy. Suspected cases were confirmed by dermatologists. Data obtained from the campaign was analyzed and results presented as cost per patient. Results: The team screened 4526 families that included 21472 persons in the Lamkichuha Municipality. Among them, 195 were suspected as leprosy by the health workers and referred to referral health facility for diagnosis. Three of them were confirmed as leprosy resulting the prevalence rate of 1.4 per 10,000 populations. The average cost spent per patient was NRS 250000 (2000 USD). Conclusion: The cost of diagnosis of leprosy by active case detection is high. The national programs should prioritize cost-effective modalities including the awareness raising campaigns for early diagnosis.